Only signaling modules that discriminate sharply between stimulatory and nonstimulatory inputs require basal signaling for fast cellular responses - Artomov, Mykyta (American Institute of Physics, 2010)
In many types of cells, binding of molecules to their receptors enables cascades of intracellular chemical reactions to take place (signaling). However, a low level of signaling also occurs in most unstimulated cells. Such basal signaling in resting cells can have many functions, one of which is that it is thought to be required for fast cellular responses to external stimuli. A mechanistic understanding of why this is true and which features of cellular signaling networks make basal signaling necessary for fast responses is unknown. We address this issue by obtaining the time required for activation of common types of cell signaling modules with and without basal signaling. Our results show that the absence of basal signaling does not have any dramatic effects on the response time for signaling modules that exhibit a graded response to increasing stimulus levels. In sharp contrast, signaling modules that exhibit sharp dose-response curves which discriminate sensitively between stimuli to which the cell needs to respond and low-grade inputs (or stochastic noise) require basal signaling for fast cellular responses. In such cases, we find that an optimal level of basal signaling balances the requirements for fast cellular responses while minimizing spurious activation without appropriate stimulation.